The effect of Dictogloss Technique on the students’ writing skill - Dian Pertiwi; Ngadiso Ngadiso; Nur Arifah Drajati (Studies in English Language and Education, 2018)
Dictogloss can be considered as way for integrating form and meaning in the learning context. The main objective of this research is to analyze whether: (1) Dictogloss is more effective than Direct Instruction to teach writing for the eleventh grades students, and (2) students having high motivation have better writing skill than those having low motivation for the eleventh grade students. This article refers to an experimental study on the effectiveness of Dictogloss to teach writing skill at one of Islamic School in Surakarta, Indonesia. The sampling used in this research was cluster random sampling with two classes as sample, namely the experimental class taught using Dictogloss and the control class taught using Direct Instruction. To collect the data, there were two instruments used in this research namely, the writing test and the motivation questionnaire. After treatment was given to both classes in eight meetings, a post test of writing to obtain data was conducted. The data were analyzed by using 2x2 Multifactor Analysis of Variance (ANOVA). Before conducting the ANOVA test, pre-requisite test namely normality and homogeneity test were conducted. The result of this research shows that: (1) Dictogloss is more effective than Direct Instruction to teach writing, and (2) students having high motivation have better writing skill than those having low motivation. Therefore, it is recommended for the English teacher to apply Dictogloss in writing activity to promote an effective teaching on writing skill. In conclusion, Dictogloss can be used to improve students’ writing skill for the eleventh grade students.